De federaties van gemeenten, de agglomeratieraad, de kulturele kommissie - Vandervelde, Jacques; Rijmenans, Arnold; Depotter, René (Brussel: BSP-federatie Brussel, 1974)
"door Jacques Vandervelde, Arnold Rijmenans, René Depotter"